Determinants of Interest in Using E-Library of Ganesha University of Education Students - SUGITA, Wayan; TRIANASARI, Trianasari; RAHMAWATI, Putu Indah (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine the effect of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit on the intention to use the E-Library by Ganesha University of Education students. The research method used is quantitative research. The population of this research is the students of Ganesha University of Education. Determination of the sample using the non probability sampling method, with the purposive sampling technique, where the sample is determined by selecting students who come to the library and students who have used the E-Library. The data in this study used a questionnaire as a data collection instrument consisting of 28 (twenty-eight) question items. The data were tested using SPSS version 20. The results showed that: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value and habit have a positive and significant effect on the interest in using the E-Library by students of the Ganesha University of Education. Therefore, the indicators for each variable can be used as a reference in the development of the E-Library by the Ganesha University of Education Library so that students' interest in using the E-Library will increase.